Pretty Pru - Dunbar, Polly (Somerville, Mass. : Candlewick Press, 2009)
Pru finds it hard to believe that her friends would steal her green handbag with the red spots, but the proof seems clear when they show up wearing the evidence.
"A Tilly and friends book"--Cover.
1.5
K-3
Keywords: Animals -- Juvenile fiction; Friendship -- Juvenile fiction; Theft -- Juvenile fiction; Animals -- Fiction; Friendship -- Fiction; Stealing -- Fiction; Animals -- Fiction; Friendship -- Fiction; Theft -- Fiction